A model of human knee ligaments in the sagittal plane. Part 2: Fibre recruitment under load. - Zavatsky, A; O'Connor, J (1992)
A mathematical model of the knee ligaments in the sagittal plane is used to study the forces in the cruciate and collateral ligaments produced by anterior/posterior tibial translation. The model is based on ligament fibre functional architecture. Geometric analysis of the deformed configurations of the model ligaments provides the additional compatibility conditions necessary for calculation of the statically indeterminate distributions of strain and stress within the ligaments and the sharing of load between ligaments. The investigation quantifies the process of ligament fibre recruitment, which occurs when fibres made slack by passive flexion/extension of the knee stretch and change their spatial positions in order to resist applied loads. The calculated ligament forces are in reasonable agreement with experimental results reported in the literature. The model explains some subtleties of ligament function not incorporated in models that represent the ligaments by a small number of lines.